The Effects of Cutting Parameters on the Characteristics of Chip and Cutting Force in High-Speed Milling of A6061 Aluminum Alloy - Pham, Thi Hoa; Nguyen, Duc Toan (Old Journal, 2018)
This paper studied the effects of cutting parameters (cutting speed, cutting depth, feed-rate) on the characteristics of chip and cutting force in high-speed milling of A6061 aluminum alloy using FEM with ABAQUS/Explicit commercial software. First, a FE model was created based on the Bao-Wierzbicki (B-W) material fracture model, which was extended from the Morh-Coulomb criteria. The simulation model was verified by comparing the morphologies of simulated chip and that obtained by SEM. Then, the effects of cutting paramters on the chip morphology, chip shrinkage coefficient and cutting force were investigated. The simulation results showed that the chip morphology significantly depends on the cutting speed. The explicit formulae, which reflect the relationship between cutting parameters on chip chip shrinkage coefficient and cutting force, were finally proposed.